2022
DOI: 10.1002/chem.202202161
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Polarization Change of Mononuclear Valence Tautomeric Cobalt Complexes Through the Use of Enantiopure Ligand

Abstract: The crystallization of a complex having electron transfer properties in a polar space group can induce the polarization switching of a crystal in a specific direction, which is attractive for the development of sensors, memory devices, and capacitors. Unfortunately, the probability of crystallization in a polar space group is usually low. Noticing that enantiopure compounds crystallize in Sohncke space groups, this paper reports a strategy for the molecular design of non‐ferroelectric polarization switching cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Currently, experimental measurement of thermally- and photoinduced polarization switching behaviors and quantitative analysis of polarization in the obtained polar crystals remain crucial tasks for future research. The pseudosymmetric crystallization we presented here offers the following advantages over conventional single enantiomer crystallization: , our method allows for the generation of polar crystals from the original nonpolar structures of racemic crystals and enables the systematic adjustment of material functions through atomic substitutions. Additionally, crystallization via combinations of pseudoenantiomers with differing presence or absence of targeted molecular properties facilitates the easy induction of polarity into specific material properties.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, experimental measurement of thermally- and photoinduced polarization switching behaviors and quantitative analysis of polarization in the obtained polar crystals remain crucial tasks for future research. The pseudosymmetric crystallization we presented here offers the following advantages over conventional single enantiomer crystallization: , our method allows for the generation of polar crystals from the original nonpolar structures of racemic crystals and enables the systematic adjustment of material functions through atomic substitutions. Additionally, crystallization via combinations of pseudoenantiomers with differing presence or absence of targeted molecular properties facilitates the easy induction of polarity into specific material properties.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subsequent research in the case of mononuclear cobalt complexes has demonstrated its efficacy in diversifying polar crystals with VT behavior. 2,40,52 However, the previously used crystallization strategy is invalid for dinuclear systems with homochiral ligands due to the lack of complementary interactions. Therefore, the [Co II Co III ] complex with an enantiopure SS-cth ligand was first investigated (cth = (7S,14S)-5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane) to aid in our initial screening.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, valence tautomeric (VT) molecules are ideal structural motifs exhibiting variable electronic configurations responsive to temperature, pressure, and external fields. 13–48 Furthermore, for crystalline materials with switchable macroscopic polarization, it is imperative that the target molecules crystallize in polar space groups so that their dipole moments will not be canceled. To date, there have been only a few non-ferroelectric molecular crystals exhibiting macroscopic polarization switching via electron transfer owing to the difficulties in crystal engineering to align molecules in polar space groups.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Valence tautomeric (VT) compounds, which possess two nearly degenerate electronic states resulting from a charge transfer process between transition metal ions and redox-active ligands, exhibit desirable properties such as switchable valence, spin multiplicity, and polarization. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The rich chemical tailorability in the molecular design and properties of VT compounds renders them highly attractive for the development of a wide variety of functional materials. 5,13 Among a variety of external stimuli, light has received extensive research in recent years due to its fast response and remote control.…”
mentioning
confidence: 99%